GEOMETRIC SHAPE OF UNBALANCE MECHANICAL CENTRIFUGAL VIBRATION EXITER OF OSCILLATIONS - Жигилій, С. М.; Пісковий, С. С. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The research of the influence of geometric shape of unbalance mechanical centrifugal vibration exciter on the general dynamic impact of the vibration exciter was expounded; its optimal geometric shape was set out of a fixed value of the radius of the unbalance; possible options were considered. Keywords:centrifugal force of inertia unbalance ofvibration exciter, the geometric shape of the unbalance, controlled mechanical centrifugal unbalanced vibration exciters of oscillations (CMCUVEO), optimization mathematical model, the objective (target) function.